2022
DOI: 10.1212/wnl.0000000000200936
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based, Implementable Motor Rehabilitation Guidelines for Individuals With Cerebral Palsy

Abstract: Background:Cerebral palsy is a life-long condition that causes heterogeneous motor disorders. Motor rehabilitation interventions must be adapted to the topography of the symptoms, ambulatory capacity and age of the individual. Current guidelines do not differentiate between the different profiles of individuals with cerebral palsy, which limits their implementation.Objectives:To develop evidence-based, implementable guidelines for motor rehabilitation interventions for individuals with cerebral palsy according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Difficulty executing bimanual tasks is one of the greatest causes of functional impairment for these children because it impacts their participation and quality of life [ 6 8 ]. Furthermore, since new, innovative therapies focus on developing and training bimanual performance to improve participation in daily life activities [ 9 ], validated evaluation of bimanual movements has become crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Difficulty executing bimanual tasks is one of the greatest causes of functional impairment for these children because it impacts their participation and quality of life [ 6 8 ]. Furthermore, since new, innovative therapies focus on developing and training bimanual performance to improve participation in daily life activities [ 9 ], validated evaluation of bimanual movements has become crucial.…”
Section: Introductionmentioning
confidence: 99%
“…1 Constraint-induced movement therapy (CIMT) has been shown to result in an improvement in bimanual performance and unimanual capacity in children with unilateral CP, however, the quality of evidence is low. 2,3 Moreover, the effect sizes are modest, with a mean difference (MD) of 5.44 Assisting Hand Assessment (AHA) units and MD ranging from 5.95 to 12.54 across various domains of the Quality of Upper Extremity Skills Test (QUEST). 2 Given these modest effect sizes, there is a need to explore additional neurorehabilitation measures like neuromodulation, in this population.…”
Section: Introductionmentioning
confidence: 99%
“…The meta-analysis by Oskoui et al 3 showed that the international prevalence rate of children with cerebral palsy was 0.21%. In China, the prevalence of CP among children younger than 7 yrs is 1.6 per 1000 children, and the estimated total number of children living with CP in China is 310,000 4 …”
mentioning
confidence: 99%
“…In China, the prevalence of CP among children younger than 7 yrs is 1.6 per 1000 children, and the estimated total number of children living with CP in China is 310,000. 4 In recent decades, the neonatal mortality rate and incidence of stillbirth have decreased significantly because of the development of medicine. However, the incidence of CP has not decreased, and the proportion of patients with severe CP has increased.…”
mentioning
confidence: 99%